Democratic Crisis in the 21st Century and Research Challenges in Public Administration - Santos, Elisabete; Rossi, Renata Alvarez (Organizacoes & sociedade, 2023)
Abstract Public administration research is constantly challenged to reflect on the complex relations between administration and democracy. The national and international reemergence of far right political forces, which use democratic ground rules as tools against classic liberal democracy, poses additional theoretical and epistemological challenges to the field. Which knowledge production challenges and perspectives appear in the field of administration, especially regarding the articulation between management models and democracy, considering society projects and development models? Such a debate requires mobilizing critical knowledge, redesigning study subjects, reframing participation, deepening the interdisciplinary character of research, and clarifying the political dimensions of the relationship between res publica and democracy. Resumo A pesquisa no campo da administração pública encontra-se permanentemente desafiada a refletir sobre a complexa relação que envolve a administração e democracia. O retorno ao cenário nacional e internacional de forças políticas situadas no campo da extrema direita, que recorrem às regras do jogo democrático como ferramentas contra a clássica democracia liberal, coloca desafios teórico-epistemológicos adicionais ao campo. Quais os desafios e perspectivas da produção do saber no campo da administração, particularmente no que diz respeito à articulação entre modelos de gestão e democracia, considerando projetos de sociedade e modelos de desenvolvimento? Esse debate requer a mobilização de conhecimento crítico, o redesenho de objetos de estudo, do significado da participação, o aprofundamento do caráter interdisciplinar da pesquisa, além de explicitar a dimensão política da relação entre res publica e democracia.